Morphosyntax and logical abilities in Italian poor readers: The problem of SLI under-identification. Issue 3 (June 2016) - Arosio, Fabrizio; Pagliarini, Elena; Perugini, Maria; Barbieri, Lina; Guasti, Maria Teresa
The study investigated morphosyntactic abilities and semantic-pragmatic competence in 24 children with developmental dyslexia aged 7 -12 years. Morphosyntactic abilities were investgated in a direct object clitic production task, semantic-pragmatic competence in a quantifier comprehension task. Children with dyslexia produced fewer clitics than their age controls and vocabulary controls. Ten children with dyslexia scored less than 1.5 SD below the mean score of an additional group of 89 children of the same age, selected across a range of oral and reading abilities. No difference was found in quantifier comprehension. These findings suggest that a large number of children with dyslexia are likely to be affected by SLI, although not diagnosed, and the authors recommend language assessment, including assessment of clitic production, when children are referred for dyslexia. By capitalizing on theories that see SLI as a deficit in the processing of complex aspects of linguistic relations, the authors argue that the production of clitics is particularly challenging because of their syntactic and morphosyntactic complexity.